2014
DOI: 10.17221/109/2013-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

An EST-SSR marker, bu099658, and its potential use in breeding for yellow rust resistance in wheat

Abstract: Hasancebi S., Mert Z., Ertugrul F., Akan K., Aydin Y., Senturk Akfirat F., Altinkut Uncuoglu A. (2014): An EST-SSR marker, bu099658, and its potential use in breeding for yellow rust resistance in wheat. Czech J. Genet. Plant Breed., 50: 11-18.EST-SSR markers, derived from the A and B genomes of wheat were used to identify molecular markers associated with yellow rust resistance. For this purpose, bulk segregant analysis was performed using 114 EST-SSR primer pairs. They were screened on the parent genotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…An EST-SSR marker, BU099658 and STM marker, Stm673acag (1.1 cM linkage with Yr1 gene) were used to identify this gene in 74 wheat genotypes. The expected fragment size for BU099658 marker was 206 bp (Hasancebi et al, 2014). In the present study, the marker amplified DNA fragment sizes of 157 to 206 bp.…”
Section: Yellow Rust Resistant Gene Yr1supporting
confidence: 49%
See 1 more Smart Citation
“…An EST-SSR marker, BU099658 and STM marker, Stm673acag (1.1 cM linkage with Yr1 gene) were used to identify this gene in 74 wheat genotypes. The expected fragment size for BU099658 marker was 206 bp (Hasancebi et al, 2014). In the present study, the marker amplified DNA fragment sizes of 157 to 206 bp.…”
Section: Yellow Rust Resistant Gene Yr1supporting
confidence: 49%
“…Bansal et al (2009) reported a molecular marker, stm673acag, that amplified 120 and 124 bp products in most lines carrying Yr1 gene, but in the present study the marker amplified a 129 bp fragment size, which may be due to technical reasons. Hasancebi et al (2014) reported the second marker, bu099658 that is linked to Yr1 gene. This marker amplified 206 bp only in those lines that possessed Yr1 genes, including Yr1/6*Avocet S. However, this marker amplified 162 bp product on the positive control (Yr1*Avocet S).…”
Section: Discussionmentioning
confidence: 99%
“…Yr1, is mapped on chromosome 2AL. SSR markers have been used for haplotyping of this gene [38,41,61] in many wheat materials and various levels of detection frequencies were reported. With the KASP SNP marker IWB81533, no detection was achieved in the present study.…”
Section: Kasp Assay Based Screening For Known Yr Genesmentioning
confidence: 99%